2005
DOI: 10.7863/jum.2005.24.10.1365
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Medical Students Diagnostic Sonography

Abstract: Training in sonography for medical students could be used as a foundation for later, more specialty-specific training to improve the overall medical sonography skills for all physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 8 publications
2
66
1
4
Order By: Relevance
“…A few medical schools have performed pilot projects teaching ultrasound to smaller groups of students with class sizes ranging from 5-176 students. [6][7][8][9][10][11][12][13][14] Unlike our project, most of these schools limited ultrasound teaching to senior medical students. [7][8][9][10] Two medical schools that taught ultrasound early in the medical school curriculum restricted it to anatomy courses without bedside clinical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few medical schools have performed pilot projects teaching ultrasound to smaller groups of students with class sizes ranging from 5-176 students. [6][7][8][9][10][11][12][13][14] Unlike our project, most of these schools limited ultrasound teaching to senior medical students. [7][8][9][10] Two medical schools that taught ultrasound early in the medical school curriculum restricted it to anatomy courses without bedside clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] Unlike our project, most of these schools limited ultrasound teaching to senior medical students. [7][8][9][10] Two medical schools that taught ultrasound early in the medical school curriculum restricted it to anatomy courses without bedside clinical applications. 9,11 However, this study demonstrates the feasibility and acceptability of ultrasound use among second year students in an integrated physical diagnosis course.…”
Section: Discussionmentioning
confidence: 99%
“…This was reaffirmed in focus groups where students commented that the haptic experience of scanning their peers aided image orientation and interpretation. Several pilot studies 19,[22][23][24][25] and studies with student cohorts 5,7,18,26 show that, with focussed training, students can gain sufficient scanning proficiency for clinical examination. However, Sweetman et al 12 caution that infrequent scanning opportunities encourage confidence without skill development, since ultrasound scanning did not improve students' performance in clinical examinations.…”
Section: Introduction To Pu As An Imaging Technology and A Teaching Toolmentioning
confidence: 99%
“…To date, physician education in diagnostic sonography was previously withheld until residency and varied widely between specialties. [25] Studies [26][27][28] showed that pre-clinical medical students can obtain a residentlevel understanding of ultrasonography given proper means and methods of training. Specifically in Tanzania, previous studies [24,29] have demonstrated the importance of ultrasound in low-resource settings and the success of training programs in rural Tanzanian hospitals and clinics.…”
Section: Discussionmentioning
confidence: 99%